2007
DOI: 10.1021/es062559q
|View full text |Cite
|
Sign up to set email alerts
|

Producing Bio-Based Bulk Chemicals Using Industrial Biotechnology Saves Energy and Combats Climate Change

Abstract: The production of bulk chemicals from biomass can make a significant contribution to solving two of the most urgent environmental problems: climate change and depletion of fossil energy. We analyzed current and future technology routes leading to 15 bulk chemicals using industrial biotechnology and calculated their CO 2 emissions and fossil energy use. Savings of more than 100% in nonrenewable energy use and greenhouse gas emissions are already possible with current state of the art biotechnology. Substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(131 citation statements)
references
References 16 publications
2
127
0
2
Order By: Relevance
“…A growing number of environmental assessments of bio-materials include land use in their analyses (see Dornburg et al 2003;Hermann et al 2007;Kim and Dale 2005b) and methodological work is under way (see e.g. Jolliet et al 2003;Kloverpris et al 2008;Mila i Canals et al 2007) but has not yet established one single accepted methodology in terms of how different types of land use should be compared.…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of environmental assessments of bio-materials include land use in their analyses (see Dornburg et al 2003;Hermann et al 2007;Kim and Dale 2005b) and methodological work is under way (see e.g. Jolliet et al 2003;Kloverpris et al 2008;Mila i Canals et al 2007) but has not yet established one single accepted methodology in terms of how different types of land use should be compared.…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
“…In the context of long-term emission targets, one of the important issues is to what extent bio-based materials score better in environmental terms compared to petrochemical polymers. Several studies have already been carried out regarding the environmental advantages or disadvantages of using novel biopolymers such as PLA (Vink et al 2003;Vink et al 2007), bio-based polyethylene (Hermann et al 2007) or polyhydroxyalkanoates (Kim and Dale 2005a), concluding that there are environmental advantages for some bio-based materials and that other materials could become advantageous if technologies used in their production improve and progress. So far, these studies have focussed on comparing quantities of materials (e.g.…”
mentioning
confidence: 99%
“…Many analyses indicate that rather than grains or seeds, crop residues and purpose-grown crops that produce large amounts of biomass per acre will be more efficient and have the greatest environmental benefits (Schmer et al 2008;Adler et al 2007 Biomass may also be an efficient petroleum substitute for uses other than transportation fuel. For example, Hermann et al (2007) and Ragauskas et al (2006) reported that bio-based bulk organic chemicals offer clear environmental and energetic advantages compared to petroleum as a feedstock. This comes in part from avoiding expensive oxygenation and catalytic steps to convert petroleum into alcohols, carboxylic acids and esters.…”
Section: Best Biomass Crops and Usesmentioning
confidence: 99%
“…Technological advances in biocatalyst discovery, bioprocess optimization, and product recovery are important considerations for the impact of industrial or white biotechnology that promotes a wider use of microbial or bio-based production of goods and services (Hermann and Patel 2007;Caesar 2008). In this study, we carried out whole-cell biocatalysis in organic-aqueous two-phase partitioning bioreactors (TPPB) systems to test the feasibility of bioproduction of two water-insoluble products.…”
Section: Introductionmentioning
confidence: 99%